Deliberação colegiada de conflito: o método alternativo de solução de controvérsias entre usuários no sistema nacional de gerenciamento de recursos hídricos e o ODS 16 - Silva, Victor Athayde (2023)
This research focus on Brazil’s Law 9433/1997 that created the National Water Resources Policy, institutionally executed by the National Water Resources Management System (SINGREH in Portuguese), and established a public, but nonstate-operated, water management system in the country (through the creation of collegiate bodies with multiple stakeholders’ participation). It’s important to understand that water is a fundamental human right and, therefore some it’s important to have multiple levels of participation in the management of this scarce and economically valuable resource. As a limited natural resource, but with several different uses, it has a high potential for conflicts, and, according to the National Water Resources Policy, the collegiate bodies (mentioned bellow) should solve all the conflicts that arise from users within the hydrographic basin. However, it’s important to understand if this body would have adequate institutional dimension of state capacity to solve conflicts by using alternative dispute resolution systems and avoid taking cases to the overloadedcourts of Brazil, and undermines the credibility of the judiciary and the democratic rule of law itself. This research aims to analyze a significant national repercussion conflict and the mechanisms that took place in forms of participatory democracy by several institutions that are part of the SINGREH, but not through the judiciary. It is also important to understand nowadays, from a perspective of the United Nations' Sustainable Development Goals, especially SDG16, especially in terms of strengthening institutions by resolving conflicts. Finally, it shows which SINGREH collegiate body would be competent to regulate conflict resolution within the scope of the PNRH.